Does income inequality affect green innovation? A non-linear evidence - Zou, Xing-Yun; Peng, Xin-Yu; Zhao, Xin-Xin; Ma, Jie; Chang, Chun-Ping (Technological and Economic Development of Economy, 2024)
It is crucial for the advancement of political economics and innovation economics to examine the relationship between income inequality and green innovation (GI). Using the panel fixed effect model, this study investigates the influence of income inequality on GI across 97 countries from 1991 to 2018 and demonstrates a significant non-linear association between the two. The empirical data exhibit an inverted U-shape relationship, suggesting that there is an optimal degree of income inequality that optimizes GI output, and the inflection point of our overall sample is at a Gini coefficient of 0.366. Additionally, we choose a set of robustness tests to validate the results by substituting explained variables, adding omitted variables, and employing the difference and system generalized method of moments (GMM) estimations. Moreover, heterogeneity analysis reveals that the non-linear patterns vary among samples, with the U-shape relationship being more significant in countries with lower income, higher corruption, and weaker government effectiveness. Our findings provide government decision-makers with a crucial reference for maximizing the importance of income distribution in fostering GI and achieving sustainable development.First published online 24 August 2023